TRPM4 in cerebral artery smooth muscle cells - Gonzales, Albert Louis, author; Earley, Scott, advisor; Amberg, Gregory C., committee member; Dinenno, Frank A., committee member; Rash, John E., committee member; Tamkun, Michael M., committee member (Colorado State University. Libraries, 2012)
Cerebral arterial tone is dependent on the depolarizing and hyperpolarizing currents regulating membrane potential and governing the influx of Ca2+ needed for smooth muscle contraction. Several ion channels have been proposed to contribute to membrane depolarization, but the underlying molecular mechanisms are not fully understood. In this review, we will discuss the historical and physiological significance of the Ca2+-activated cation channel, TRPM4, in regulating membrane potential of cerebral artery smooth muscle cells. As a member of the recently described transient receptor potential super family of ion channels, TRPM4 possesses the biophysical properties and upstream cellular signaling and regulatory pathways that establish it as a major physiological player in smooth muscle membrane depolarization.
Keywords: calcium; TRPM4; smooth muscle cells; myogenic response